Дослідження верстата з паралельною кінематикою - Колісниченко, В’ячеслав Романович; Kolisnychenko, Viacheslav (ЦНТУ, 2024)
Метою роботи є дослідження впливу геометричних параметрів кінематичних ланок верстата з паралельною кінематикою на переміщення його виконавчого органу. В роботі проведено аналіз компоновок верстатів з паралельною кінематикою, їх переваг і недоліків. Також вирішено пряму і зворотну задачу кінематики для верстата з паралельною кінематикою типу «ножиці». Розглянуто узгодженість рухів кінематичних ланок при реалізації типових рухів виконавчого органу. Проаналізовано можливість здійснення виконавчим органом вертикальних і горизонтальних рухів при різних геометричних параметрах кінематичних ланок. Виконано необхідні економічні розрахунки. Актуальність: досліджено вплив геометричних параметрів кінематичних ланок верстата з паралельною кінематикою на переміщення його виконавчого органу. Практичне значення: вирішено пряму та зворотну задачі кінематики для верстата з паралельною кінематикою типу «ножиці». The purpose of the work is to study the influence of the geometric parameters of the kinematic links of a machine with parallel kinematics on the movement of its executive body. The paper analyzes the layouts of machines with parallel kinematics, their advantages and disadvantages. The direct and inverse problem of kinematics for a machine with parallel kinematics of the "scissors" type has also been solved. The coherence of the movements of kinematic links during the implementation of typical movements of the executive body is considered. The possibility of the executive body performing vertical and horizontal movements with different geometric parameters of the kinematic links was analyzed. Necessary economic calculations have been performed. Relevance: the effect of the geometric parameters of the kinematic links of the machine tool with parallel kinematics on the movement of its executive body was investigated. Practical significance: direct and inverse kinematics problems are solved for a machine with parallel kinematics of the "scissors" type.
Study of a machine with parallel kinematics
Keywords: паралельна кінематика; верстат; кінематичний аналіз; робочий простір; parallel kinematics; machine tool; kinematic analysis; working space